KAJIAN KARAKTERISTIK KIMIA AIR, FISIKA AIR DAN DEBIT SUNGAI PADA KAWASAN DAS PADANG AKIBAT PEMBUANGAN LIMBAH TAPIOKA - Riyanda Agustira; Kemala Sari Lubis; jamila Jamila (Universitas Sumatera Utara, 2013)
The source of liquid waste of tapioca industry from leaching and evaporation. Normally that liquid waste contents rough and soft of suspension solid and organic matter. Accumulation continuously of liquid waste of tapioca industry cause bad taste and odor so can destroy environment. The research executed on 5 tapioka factory at watershed Padang area and aroundabout used a survey method. The research was conducted by water sampling at 3-5 outlets, first from point of exile source of liquid waste to mixed at stream of river-bed. Water sampling used intergrating depth system method, in this researh at water surface of river stream. Water samples were taken three (3) replications for each outlet. Parameters were measured pH, TSS TDS, BOD, COD and velocity of water. The research result to point at stream river waste of tapioca factory outlet PT. Serasi Jaya to point at increase value at some parameters to exceed standard quality class that on pH, TSS, and COD parameters each 4,23, 8,80 mg/L, and 137 mg/L. At stream river water waste of tapioca factory outlet PT. Sumatera Telaga Tapioka find some parameters to exceed standard quality class on parameters value pH, TSS, COD each 4,48, 79,3 mg/L, 1045,2 mg/L. At stream river water waste of tapioca factory outlet PT. Deli Sari Murni find some parameters to exceed standart quality class on TSS and COD parameters each 84,67 mg/L and 167,27 mg/L. Key words : tapioca waste, chemical caharacteristic and velocity